Apheresis therapies in MOGAD: a retrospective study of 117 therapeutic interventions in 571 attacks - Schwake, Carolin; Ladopoulos, Theodoros; Häußler, Vivien; Kleiter, Ingo; Ringelstein, Marius; Aktas, Orhan; Kümpfel, Tania; Engels, Daniel; Havla, Joachim; Hümmert, Martin W.; Kretschmer, Julian Reza; Tkachenko, Daria; et al. (Journal of neurology, neurosurgery, and psychiatry, 2025)
Background Incomplete attack remission is the main cause of disability in myelin oligodendrocyte glycoprotein antibody-associated disease (MOGAD). Apheresis therapies such as plasma exchange and immunoadsorption are widely used in neuroimmunology. Data on apheresis outcomes in MOGAD attacks remain limited. - Methods We retrospectively evaluated all apheresis treated attacks occurring in patients with MOGAD between 2008 and 2023 at 18 Neuromyelitis Optica Study Group centres. Treatment response was categorised as complete, partial or no remission. Preattack and follow-up Expanded Disability Status Scale (EDSS) and visual Functional System Scores (FSS) were used to calculate absolute outcomes (ΔEDSS/Δvisual FSS). Predictors of complete remission were analysed using a generalised linear mixed model. - Results Apheresis was used for 117/571 (20.5%) attacks in 85/209 (40.7%) patients. Attacks with simultaneous optic neuritis and myelitis were treated more often with apheresis (42.4%, n=14) than isolated myelitis (25.2%, n=35), cerebral manifestation (21.0%, n=17) or isolated optic neuritis (17.6%, n=51). Apheresis was initiated as first-line therapy in 12% (4.5 (IQR 0-11) days after attack onset), second-line therapy in 62% (15 (IQR 6.75-31) days) and third-line therapy in 26% (30 (IQR 19-42) days). Complete remission was achieved in 21%, partial remission in 70% and no remission in 9% of patients. First-line apheresis (OR 2.5, p=0.040) and concomitant disease-modifying therapy (OR 1.5, p=0.011) were associated with complete remission. Both parameters were also associated with a favourable ΔEDSS. No differences in outcomes were observed between the apheresis types. - Conclusion Apheresis is frequently used in MOGAD attacks. An early start as first-line therapy and concomitant disease-modifying therapy predict full attack recovery.
Online veröffentlicht: 4. November 2024
Gesehen am 10.09.2025